Mengoptimalkan Pembelajaran Bagi Anak Dengan Adhd Melalui Pendekatan Inklusif di Sekolah Dasar - Septy Nurfadhillah; Andini Aqmarani; Eka Yulyawan Kurniawan; Devi Fitriya; Emaliah Samhatul Ulyah; Melia Gita Andreani; Nazwakhairy Putri Syahra; Nur Fauziyah Fadhillahwati; Pujianti; Rahma Azzahra Putri; Rizkia Dwi Lestari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Inclusive education has become a focus of attention in supporting the successful learning of all students, including those with Attention Deficit Hyperactivity Disorder (ADHD). Children with ADHD face special challenges in managing their attention, impulsivity, and energy, requiring appropriate learning approaches. This research aims to investigate and identify the optimal implementation of an inclusive approach in supporting the learning of children with ADHD in elementary schools. Qualitative research methods were used to explore the experiences of educators, school staff, and parents in facing the learning challenges of children with ADHD. The results show that inclusive approaches implemented in elementary schools can play a key role in creating a supportive learning environment for children with ADHD.